Influence of pH Solution on the Electrodeposition of Tungsten Oxide (WO3) Films onto Indium Tin Oxide (ITO)-glass Substrate - Shahizuan, Wan Danial; Mohd, Yusairie (Journal of Science and Technology, 2012)
An investigation on the influence of pH solution on the formation of tungsten oxide (WO3) films on indium tin oxide (ITO) - coated glass substrate was carried out. The films have been electrochemically deposited from bath solution containing Na2WO4.2H2O and H2O2 at different pH values using constant potential of -0.45V vs Ag/AgCl for 300s. The surface morphology and crystalline structure of the prepared films were characterized by field emission scanning electron microscope (FESEM) and X-ray diffraction (XRD), respectively. The electrochemical behaviour of the films in 1 M HNO3 was measured by cyclic voltammetry (CV). It was observed that the morphology and electrochemical behavior of WO3 films strongly depend on pH value. A smooth and thin WO3 film was deposited on ITO from pH solution of 1.30; however, the deposition at lower pH value (i.e.: pH=0.80) under the same electrodeposition conditions has produced a porous and thick film. The porous film has greatly enhanced the electrochemical behaviour of WO3 for intercalation and deintercalation of H+ ions due to its high surface area.